Negative electrode material, secondary battery and electric equipment

By using a composite matrix of porous carbon matrix and graphite material in lithium-ion batteries, combining silicon-based material and carbon cladding, the problem of insufficient conductivity and structural stability of the negative electrode material is solved, and high energy density and good cycle stability are achieved. The negative electrode material reduces economic costs.

CN119208565AInactive Publication Date: 2024-12-27SOUTH CHINA UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411336781.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrical conductivity, structural stability and energy density of the negative electrode materials of existing lithium-ion batteries are insufficient, resulting in poor cycle stability and high economic costs.

Method used

A composite matrix of porous carbon matrix and graphite material is used, combined with silicon-based material and carbon cladding, and a negative electrode material with high conductivity and structural strength is formed through specific differential curve peak strength ratio control.

Benefits of technology

It significantly improves the electrochemical performance of the negative electrode material, improves cycle stability and energy density, reduces material costs, and provides higher first-term effects and broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059068660000161
    Figure BDA0005059068660000161
  • Figure BDA0005059068660000162
    Figure BDA0005059068660000162
  • Figure BDA0005059068660000171
    Figure BDA0005059068660000171
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to a negative electrode material, a secondary battery and electric equipment. According to the negative electrode material provided by the invention, the matrix comprises the composite material of the porous carbon matrix and the graphite, so that the conductivity of the negative electrode material can be improved, the structural strength is enhanced, and the material cost is reduced; the silicon-based material is uniformly dispersed in the pore channels of the matrix, and the porous structure can provide a buffer space for the volume expansion effect of silicon, so that the expansion effect of the material is greatly reduced, and the cycle performance is improved; the carbon layer structure can reduce side reaction between the electrolyte and the active material and reduce excessive formation of an SEI film, so that the first efficiency is improved, the structural strength of the negative electrode material can be enhanced, and the cycle performance of the material is improved. The specific value of the peak intensity at the specific position is limited to be within a reasonable range, the surface floating silicon degree of the porous carbon can be controlled, silicon is deposited in pores of the porous carbon, surface floating silicon is reduced, the silicon grain size is reduced, and the material performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of new energy materials, and specifically relates to a negative electrode material, a secondary battery and an electrical device. Background Art

[0002] With the rapid development of new energy electric vehicles in recent years, higher demands have been placed on the range of lithium-ion batteries. However, the energy density of current mainstream lithium-ion batteries is difficult to meet the growing demand for large-scale energy storage in electric vehicles.

[0003] The theoretical energy density of a battery mainly depends on the specific capacity of the positive and negative electrodes and the potential difference between the two electrodes. Compared with positive electrode materials, negative electrode materials have greater room for capacity improvement, so the development of negative electrode materials with ultra-high specific capacity is of great practical significance.

[0004] Silicon has a high theoretical specific capacity, a low lithium insertion potential, and abundant reserves in the earth's crust, making it the most likely negative electrode material to replace commercial graphite negative electrodes. However, during the lithiation / delithiation process, its huge volume expansion causes the particles to pulverize and lose electrical contact. In addition, the fragmentation of silicon particles causes the surface SEI to continuously rupture and reform, consuming a large amount of lithium ions, resulting in poor cycle stability of the battery.

[0005] Therefore, constructing a new material structure to provide a buffer for the volume expansion of silicon materials and maintain the stability of the material structure is an important way to solve this problem. For example, the prior art discloses a technology for improving the conductivity and structural stability of materials by using carbon nanotubes. However, the improvement effect of carbon nanotubes on the conductivity and structural stability of materials is not particularly obvious, and the energy density of the material needs to be further improved. In addition, the price of carbon nanotubes is relatively high, which will increase economic costs. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present application is to overcome the defects of the negative electrode materials in the prior art, such as the need to further improve the conductivity, structural stability and energy density, so as to provide a negative electrode material, a secondary battery and an electrical device.

[0007] To this end, this application provides the following technical solutions:

[0008] According to one aspect of the present application, a negative electrode material is provided, comprising:

[0009] A substrate having a plurality of pores, wherein the substrate comprises a porous carbon substrate and a graphite material distributed in the porous carbon substrate;

[0010] a silicon-based material, at least partially distributed in the pores of the substrate;

[0011] A carbon coating layer distributed on at least a portion of the surface of the substrate;

[0012] In the dQ / dV differential curve of the button battery made of the negative electrode material, the peak intensity ratio corresponding to 0.40-0.50V and 0.25-0.40V is ≤1; wherein the differential curve is obtained by: at 20-30°C, the button battery is charged and discharged at a rate of 0.1C, the cycle cut-off voltage is 0.01V-2.0V, and the dQ / dV differential curve is obtained from the delithiation curve of the first cycle.

[0013] In some optional embodiments, based on the total mass of the negative electrode material, the content of graphite material is 5wt% to 40wt%, and the content of silicon element is 20wt% to 70wt%.

[0014] In some optional embodiments, the sphericity of the negative electrode material is ≥70%, and the median particle size is 1 μm to 40 μm.

[0015] In some optional embodiments, the graphite material includes at least one of artificial graphite, flake graphite, and microcrystalline graphite;

[0016] And / or, the median particle size of the graphite material is 0.5 μm to 10 μm.

[0017] In some optional embodiments, the pore volume of the matrix is ​​greater than 0.7 cm 3 / g, average pore size is 0.1nm~20nm;

[0018] And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for ≤10wt%;

[0019] And / or, the specific surface area of ​​the negative electrode material is ≤10m 2 / g.

[0020] In some optional embodiments, the pore volume of the substrate is 0.7 to 0.95 cm 3 / g;

[0021] And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for 0.5wt% to 10wt%;

[0022] And / or, the specific surface area of ​​the negative electrode material is 1 to 10 m 2 / g.

[0023] In some optional embodiments, the silicon crystal size of the Si (111) crystal plane of the negative electrode material is 0.2 nm to 20 nm.

[0024] In some optional embodiments, in the dQ / dV differential curve, the peak intensity corresponding to the range of 0.40 to 0.50 V is 2000 to 4000 mAh·g -1 ·V -1 , the corresponding peak intensity in the range of 0.25 to 0.40 V is 4000 to 6000 mAh·g -1 ·V -1 .

[0025] According to another aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode material mentioned above.

[0026] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.

[0027] The technical solution of this application has the following advantages:

[0028] The negative electrode material provided in the present application includes: a substrate having a plurality of pores, wherein the substrate includes a porous carbon substrate and a graphite material distributed in the porous carbon substrate; a silicon-based material, at least partially distributed in the pores of the substrate; a carbon coating layer, distributed on at least a portion of the surface of the substrate; in the dQ / dV differential curve of a button battery made of the negative electrode material, the peak intensity ratio corresponding to 0.40 to 0.50 V and 0.25 to 0.40 V is ≤1; wherein the differential curve is obtained by: at 20 to 30° C., charging and discharging the button battery at a rate of 0.1C, with a cycle cutoff voltage of 0.01 V to 2.0 V, and obtaining the dQ / dV differential curve from the delithiation curve of the first cycle. The negative electrode material provided by the present application, the composition of the matrix includes a composite material of a porous carbon matrix and graphite, which can improve the conductivity of the negative electrode material, enhance the structural strength, and reduce the material cost; the silicon-based material is evenly dispersed inside the pores of the matrix, and the porous structure can provide a buffer space for the volume expansion effect of silicon, greatly reduce the material expansion effect, and improve the cycle performance; the carbon layer structure can reduce the side reaction between the electrolyte and the active material, reduce the excessive formation of the SEI film, thereby improving the first effect, and can enhance the structural strength of the negative electrode material and improve the material cycle performance; the ratio of the peak intensity at a specific position characterizes the degree of floating silicon on the porous carbon surface, and the present application can control the floating silicon degree on the porous carbon matrix surface by limiting the ratio of the peak intensity at a specific position to the above range, so that silicon is deposited inside the porous carbon pores, reducing the surface floating silicon, thereby reducing the silicon grain size and improving the material performance. Compared with the silicon-carbon material in the prior art, the electrochemical performance of the negative electrode material provided by the present application is significantly improved, with high first effect, good cycle stability and broad application prospects. DETAILED DESCRIPTION

[0029] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0030] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0031] As analyzed in the background technology, the conductivity, structural stability and energy density of the silicon-carbon negative electrode materials in the prior art need to be further improved. In order to solve these problems, the present application provides a negative electrode material, a secondary battery and an electrical device.

[0032] In a typical embodiment of the present application, a negative electrode material is provided, comprising:

[0033] A substrate having a plurality of pores, wherein the substrate comprises a porous carbon substrate and a graphite material distributed in the porous carbon substrate;

[0034] a silicon-based material, at least partially distributed in the pores of the substrate;

[0035] A carbon coating layer distributed on at least a portion of the surface of the substrate;

[0036] In the dQ / dV differential curve of the button battery made of the negative electrode material, the peak intensity ratio corresponding to 0.40-0.50V and 0.25-0.40V is ≤1; wherein the differential curve is obtained by: at 20-30°C, the button battery is charged and discharged at a rate of 0.1C, the cycle cut-off voltage is 0.01V-2.0V, and the dQ / dV differential curve is obtained from the delithiation curve of the first cycle.

[0037] In some optional embodiments, the negative electrode material is prepared into a negative electrode sheet, assembled into a button cell, and subjected to a 0.1C charge and discharge test, and a dQ / dV analysis of the delithiation curve shows that the peak intensity ratio corresponding to 0.45±0.04V and 0.3±0.04V is ≤ 1. Typically, but not limitingly, the negative electrode material is prepared into a negative electrode sheet, assembled into a half cell, and subjected to a 0.1C charge and discharge test, and a dQ / dV analysis of the delithiation curve shows that the peak intensity ratio corresponding to 0.45±0.04V and 0.3±0.04V is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1, or within the range of any of the above values.

[0038] In the present application, the ratio of peak intensity at a specific position characterizes the degree of floating silicon on the porous carbon surface. The present application can control the degree of floating silicon on the porous carbon surface by limiting the ratio of peak intensity at a specific position to the above range, so that silicon is deposited inside the pores of the porous carbon, reducing the floating silicon on the surface, thereby reducing the size of silicon grains and improving material properties. In the present application, the ratio of the above peak intensities can be tested by methods and equipment known in the art. For example, a CR2032 button cell can be used to test the electrochemical performance, wherein one pole is a mixture of prepared silicon negative electrode material, acetylene black, and polyvinylidene fluoride (mass ratio 80:10:10), and the other pole is a metal lithium sheet, and the electrolyte is 1 mol / L LiPF6 dissolved in a solvent of EC / DMC / EMC (volume ratio 1:1:1) for testing.

[0039] In some embodiments, in the dQ / dV differential curve, the peak intensity corresponding to the range of 0.40 to 0.50 V is 2000 to 4000 mAh·g -1 ·V -1 , the corresponding peak intensity in the range of 0.25 to 0.40 V is 4000 to 6000 mAh·g -1 ·V -1 In this way, the nano-silicon-based materials in the silicon-carbon negative electrode material can be uniformly deposited in the porous carbon, the size of the silicon grains in the material can be reduced, the floating silicon on the surface of the material can be controlled, and the material performance can be improved.

[0040] The negative electrode material provided by the present application, the composition of the matrix includes a composite material of a porous carbon matrix and graphite, which can improve the conductivity of the negative electrode material, enhance the structural strength, and reduce the material cost; the silicon-based material is evenly dispersed inside the pores of the matrix, and the porous structure can provide a buffer space for the volume expansion effect of silicon, greatly reduce the material expansion effect, and improve the cycle performance; the carbon layer structure can reduce the side reaction between the electrolyte and the active material, reduce the excessive formation of the SEI film, thereby improving the first effect, and can enhance the structural strength of the negative electrode material and improve the material cycle performance. The ratio of the peak intensity at a specific position characterizes the degree of floating silicon on the porous carbon surface. By limiting the ratio of the peak intensity at a specific position to the above range, the present application can control the degree of floating silicon on the porous carbon surface, so that silicon is deposited inside the porous carbon pores, reduce the surface floating silicon, thereby reducing the size of silicon grains and improving material performance. Compared with the silicon-carbon materials in the prior art, the electrochemical performance of the negative electrode material provided by the present application is significantly improved, with high first effect, good cycle stability and broad application prospects.

[0041] In some optional embodiments, based on the total mass of the negative electrode material, the content of graphite material is 5wt% to 40wt%, and the content of silicon element is 20wt% to 70wt%. Typically, non-limitingly, based on the total mass of the negative electrode material, the content of graphite material is 5wt%, 8wt%, 10wt%, 15wt%, 18wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, or in the range of any of the above values; the content of silicon element is 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, or in the range of any of the above values. By limiting the content of graphite material and silicon element to the above range, the present application can give full play to the high capacity of silicon and the high first efficiency and high conductivity of graphite, and give play to the synergistic effect of silicon-based materials and graphite materials, and the graphite material itself has high stability, which can improve the material performance, and the suitable charge and discharge potential of silicon-based materials can reduce the risk of failure caused by lithium precipitation of materials. In the present application, methods and equipment known in the art can be used to test the content of silicon and graphite in the negative electrode material. For example, an inductively coupled plasma emission spectrometer (ICP) can be used to test the silicon content in the negative electrode material. The specific testing process is: the sample to be tested is digested before treatment to make a uniform solution; the prepared sample solution is introduced into the ICP instrument; in the ICP plasma, the element is excited and produces a characteristic emission spectrum; the instrument detects and records the emission spectrum; by comparing with a standard curve or a known concentration, the content of silicon in the sample is determined. The content of graphite material can be tested by TGA method.

[0042] In some optional embodiments, the sphericity of the negative electrode material is ≥70%, and the median particle size (Dv50) is 1 μm to 40 μm.

[0043] In the present application, the sphericity is a parameter that characterizes the particle morphology. The closer the particle is to a sphere in morphology, the closer its sphericity is to 1. Typically, but not limitingly, the sphericity of the negative electrode material is 70%, 73%, 75%, 78%, 80%, 85%, 90%, 92%, 95%, or within the range formed by any of the above values; the median particle size is 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or within the range formed by any of the above values. By limiting the sphericity and median particle size of the negative electrode material to the above range, the negative electrode material can be kept with good processing performance, a more stable structure, and the integrity of the SEI structure during the cycle, thereby improving the material performance. In the present application, the sphericity and median particle size of the negative electrode material can be tested by methods and equipment known in the art. For example, the sphericity of the negative electrode material can be tested by a particle image analyzer method. The particle size Dv50 is obtained by testing with a laser particle size analyzer. Specifically, the dispersed sample is introduced into the measuring cell of the laser particle size analyzer, and the measurement program is started. The laser particle size analyzer will irradiate the sample with a laser and analyze the laser scattered by the sample. The instrument collects the scattered signal and converts it into an electrical signal, and the data is processed by the built-in software. The analysis software will provide a particle size distribution diagram and related statistical data, such as Dv10, Dv50, Dv90, etc.

[0044] In some optional embodiments, the graphite material includes at least one of artificial graphite, flake graphite, and microcrystalline graphite;

[0045] And / or, the median particle size of the graphite material is 0.5μm to 10μm, typically and non-limitingly, the median particle size of the graphite material is 0.5μm, 1μm, 2μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, or within the range of any of the above values. The present application can give play to the advantages of high conductivity of graphite by limiting the median particle size of the graphite material to the above range, form a conductive path inside the material, and improve the conductive performance of the material. In addition, the graphite particles dispersed in the carbon matrix can enhance the structural strength of the material and increase the compaction density. In the present application, the median particle size of the graphite material in the matrix can be tested by methods and equipment known in the art. For example, the sample can be cut by the CP-SEM method, and the graphite particle size can be counted by scanning electron microscopy.

[0046] In some optional embodiments, the pore volume of the matrix is ​​greater than 0.7 cm 3 / g, average pore size is 0.1nm~20nm;

[0047] And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for ≤10wt%;

[0048] And / or, the specific surface area of ​​the negative electrode material is ≤10m 2 / g.

[0049] In some optional embodiments, the pore volume of the substrate is 0.7 to 0.95 cm 3 / g; typically, but not limitingly, the pore volume of the matrix is ​​0.7cm 3 / g,0.72cm 3 / g, 0.75cm 3 / g,0.78cm 3 / g,0.8cm 3 / g,0.83cm 3 / g,0.85cm 3 / g,0.87cm 3 / g,0.9cm 3 / g,0.95cm 3 / g, or within the range formed by any of the above values; the present application limits the pore volume of the substrate to the above range, which can enable the porous carbon substrate to deposit suitable silicon and increase the material capacity. The porous structure also provides a buffer space for the volume expansion of silicon, thereby improving the electrochemical performance of the material.

[0050] And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for 0.5wt% to 10wt%;

[0051] And / or, the specific surface area of ​​the negative electrode material is 1 to 10 m 2 / g.

[0052] In some optional embodiments, based on the total mass of the negative electrode material, the mass proportion of the carbon layer is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, or within the range of any of the above values; the specific surface area of ​​the negative electrode material is 1m 2 / g,2m 2 / g,3m 2 / g,4m 2 / g,5m 2 / g,6m 2 / g,7m 2 / g,8m 2 / g,9m 2 / g,10m 2 / g, or within the range formed by any of the above values. The present application limits the carbon layer mass ratio and specific surface area of ​​the negative electrode material to the above ranges to maintain the integrity of the carbon coating layer, prevent the side reaction of the active material with the electrolyte, thereby reducing lithium consumption and excessive formation of SEI.

[0053] In the present application, the specific surface area of ​​the negative electrode material, the pore volume and average pore size of the matrix, and the mass proportion of the carbon layer in the negative electrode material can be tested by methods and equipment known in the art. For example, the specific surface area is obtained by testing a fully automatic physical adsorption instrument, specifically by drying and degassing the sample to be tested at high temperature to remove moisture and adsorbed gas in the sample pores, and then placing the pretreated sample in the sample pool of the instrument, and vacuum degassing the sample to remove the adsorbed gas on the sample surface and pores. At liquid nitrogen temperature, pure nitrogen is introduced into the sample tube for adsorption. After the adsorption is completed, the pressure of the nitrogen is gradually reduced and the desorption amount is recorded. The instrument automatically records the nitrogen adsorption and desorption amount. The adsorption isotherm is analyzed using the BET (Brunol-Emmett-Teller) theory or other appropriate models to calculate the specific surface area. According to the adsorption isotherm tested by the above method, the pore size distribution and pore volume of the material can be obtained by methods such as BJH or HK. The mass proportion of the carbon layer is obtained by the TG-DTA test method.

[0054] In some optional embodiments, the Si (111) crystal plane silicon crystal size of the negative electrode material is 0.2nm-20nm. Typically, but not limited to, the Si (111) crystal plane silicon crystal size of the negative electrode material is 0.2nm, 2nm, 4nm, 6nm, 8nm, 10nm, 13nm, 15nm, 18nm, 20nm, or within the range of any of the above values.

[0055] In the present application, the silicon crystal size of the Si (111) crystal plane of the negative electrode material characterizes the silicon crystal size in the silicon negative electrode material. In the present application, by limiting the silicon crystal size of the Si (111) crystal plane of the negative electrode material to the above range, the expansion and distortion of the silicon crystal structure during the material cycle can be reduced, and the silicon particle phase interface can be kept stable. In the present application, the silicon crystal size of the Si (111) crystal plane of the negative electrode material can be tested by methods and equipment known in the art. For example, XRD characterization can be used, combined with the Scherrer formula to calculate the silicon grain size for testing.

[0056] According to another aspect of the present application, a method for preparing the above-mentioned negative electrode material is provided, comprising the following steps:

[0057] S1, mixing a porous carbon precursor, a graphite material, an inorganic base, and a surfactant to obtain a mixed slurry;

[0058] S2, granulating the mixed slurry by spray drying to obtain a matrix precursor;

[0059] S3, carbonizing and activating the matrix precursor, washing and drying the matrix to obtain a matrix;

[0060] S4, depositing silicon-based materials in the pores of the substrate by chemical vapor deposition technology, and then carbon-coating at least a portion of the surface of the substrate to obtain a negative electrode material.

[0061] In some optional embodiments, the porous carbon precursor in S1 includes but is not limited to at least one of phenolic resin, epoxy resin, sucrose, glucose, starch, etc.; the graphite material includes but is not limited to at least one of artificial graphite, flake graphite, and microcrystalline graphite; the inorganic base includes but is not limited to at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, and calcium hydroxide; the surfactant includes but is not limited to at least one of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium dodecylbenzene sulfonate, glycerol, polyethylene glycol ether, and polysorbate.

[0062] In some optional embodiments, in S2, the spray drying temperature is 120°C-260°C, and optionally, nitrogen or inert gas protection is used during the spray drying process.

[0063] In some optional embodiments, in S3, the carbonization operation includes keeping the temperature at 200-400°C for 1-3h, heating to 600-900°C, and carbonizing for 1-5h; optionally, nitrogen or inert gas protection is used during the carbonization process;

[0064] In some optional embodiments, in S4, during the deposition of the silicon-based material, a mixture of nitrogen and silane is used for deposition, and optionally, the volume ratio of nitrogen to silane is 1:1-1:5; the deposition temperature is 350° C.-750° C., and the deposition time is 1-10 h;

[0065] In some optional embodiments, in S4, a mixed gas of nitrogen and acetylene is used for carbon coating, and optionally, the volume ratio of nitrogen to acetylene is 6:1-1:1; the temperature of carbon coating is 600-900° C., and the time of carbon coating is 0.5-10 h.

[0066] According to another aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode material mentioned above.

[0067] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.

[0068] In the present application, the negative electrode plates in the provided secondary batteries and electrical devices use the above-provided negative electrode materials as active materials. Since the above-provided negative electrode materials have excellent energy density, conductivity and structural stability, the performance of the secondary batteries and electrical devices is even better.

[0069] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0070] Example 1

[0071] A negative electrode material of this embodiment includes: a substrate having a plurality of pores, the substrate including a porous carbon substrate and a graphite material distributed in the porous carbon substrate; a silicon-based material at least partially distributed in the pores of the substrate; and a carbon coating layer distributed on at least a portion of the surface of the substrate.

[0072] The specific preparation method of the above negative electrode material comprises the following steps:

[0073] (1) Phenolic resin (manufacturer Shandong Yonghui New Materials model 9003-35-4), artificial graphite (Dv50 is 2 μm), KOH, and hexadecyltrimethylammonium bromide are dissolved and dispersed in a stirring tank at a mass ratio of 1:0.3:2:0.05 to obtain a mixed slurry;

[0074] (2) granulating the mixed slurry through a spray dryer to obtain a matrix precursor, the spray temperature is 160° C., and an inert atmosphere is used during the process;

[0075] (3) Carbonizing the matrix precursor under inert atmosphere, first heating to 300°C and keeping it for 1 hour; then heating to 800°C for carbonization and keeping it for 4 hours to obtain a black powder;

[0076] (4) washing the black powder with deionized water to remove residual alkali, filtering, and drying to obtain a matrix;

[0077] (5) The substrate obtained in step (4) is placed in a CVD furnace, and a mixture of nitrogen and silane is introduced into the furnace for silicon deposition, the volume ratio of nitrogen to silane is 1:3, the deposition temperature is 400°C, and the deposition time is 4 hours to obtain a silicon-carbon precursor. Then, the introduction of silane is stopped, and the furnace is heated to 600°C under an inert atmosphere. A mixture of nitrogen and acetylene is introduced into the furnace, and the volume ratio of nitrogen to acetylene is 4:1. The silicon-carbon precursor is carbon-coated for a coating time of 4 hours. The introduction of acetylene is stopped, and the furnace is naturally cooled to room temperature under an inert atmosphere to obtain a negative electrode material.

[0078] Example 2

[0079] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that in step (1), the phenolic resin, artificial graphite, KOH, and hexadecyltrimethylammonium bromide are mixed in a mass ratio of 1:0.07:2:0.05.

[0080] Example 3

[0081] A negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that in step (1), phenolic resin, artificial graphite, KOH, and hexadecyltrimethylammonium bromide are mixed in a mass ratio of 1:2:2:0.05.

[0082] Example 4

[0083] The negative electrode material of this embodiment is basically the same as that of embodiment 1, except that the carbonization temperature in step (3) is changed to 600°C.

[0084] Example 5

[0085] The negative electrode material of this embodiment is basically the same as that of embodiment 1, except that the carbonization temperature in step (3) is changed to 700°C.

[0086] Example 6

[0087] The negative electrode material of this embodiment is basically the same as that of embodiment 1, except that the carbonization temperature in step (3) is changed to 1000°C.

[0088] Example 7

[0089] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing silane in step (5) is changed to 6 hours.

[0090] Example 8

[0091] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing silane in step (5) is changed to 1 hour.

[0092] Example 9

[0093] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing silane in step (5) is changed to 10 hours.

[0094] Example 10

[0095] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing acetylene for carbon coating in step (5) is changed to 1 hour.

[0096] Embodiment 11

[0097] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing acetylene for carbon coating in step (5) is changed to 2 hours.

[0098] Example 12

[0099] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the time for introducing acetylene for carbon coating in step (5) is changed to 6 hours.

[0100] Embodiment 13

[0101] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the median particle size of the artificial graphite in step (1) is adjusted to 0.5 μm.

[0102] Embodiment 14

[0103] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the median particle size of the artificial graphite in step (1) is adjusted to 4 μm.

[0104] Embodiment 15

[0105] The negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the median particle size of the artificial graphite in step (1) is adjusted to 10 μm.

[0106] Example 16

[0107] The negative electrode material of this embodiment is basically the same as that of embodiment 1, except that in step (1), phenolic resin, artificial graphite, KOH, and hexadecyltrimethylammonium bromide are mixed in a mass ratio of 1:0.15:3:0.05. In step (5), the silane deposition temperature is changed to 350°C.

[0108] Embodiment 17

[0109] The negative electrode material of this embodiment is basically the same as that of embodiment 1, except that in step (1), phenolic resin, artificial graphite, KOH, and hexadecyltrimethylammonium bromide are mixed in a mass ratio of 1:0.15:1.5:0.05. In step (5), the silane deposition temperature is changed to 500°C.

[0110] Embodiment 18

[0111] A negative electrode material of this embodiment is basically the same as that of embodiment 1, except that in step (1), phenolic resin, artificial graphite, KOH, and hexadecyltrimethylammonium bromide are mixed in a mass ratio of 1:0.15:0.5:0.05. In step (5), the silane deposition temperature is changed to 750°C.

[0112] Comparative Example 1

[0113] The negative electrode material of this comparative example is basically the same as that of Example 1, except that no graphite material is added in step (1) and the temperature of the carbonization treatment is adjusted.

[0114] Comparative Example 2

[0115] The negative electrode material of this comparative example is basically the same as that of Example 1, except that acetylene is not introduced for carbon coating in step (5) and the temperature of the carbonization treatment is adjusted.

[0116] Comparative Example 3

[0117] The negative electrode material of this comparative example is basically the same as that of Example 1, except that in step (1), carbon nanotubes (tube diameter 0.5-3.5 nm, aspect ratio>1000:1) of equal mass are used instead of artificial graphite, and the temperature of the carbonization treatment is adjusted.

[0118] Test Case

[0119] The substrates, negative electrode materials and button-type batteries assembled from the negative electrode materials provided in the embodiments and comparative examples were subjected to performance tests. The specific preparation process of the button-type batteries and the battery testing method are as follows:

[0120] Preparation of button cells:

[0121] The negative electrode materials prepared by the above-mentioned embodiments and comparative examples are used to make negative electrode sheets, and then assembled into button batteries. Specifically:

[0122] 1) Preparation of negative electrode sheet: The negative electrode materials, conductive agent (carbon black), and binder (polyvinylidene fluoride, PVDF) prepared in the above examples and comparative examples were mixed at a ratio of 8:1:1, and 20 wt% of the total mixed powder solvent (N-methylpyrrolidone, NMP) was added dropwise, and stirred evenly to prepare negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector (copper foil), and the coating surface density was about 4 mg / cm 2 The coated negative electrode sheet is dried to remove the solvent. The dried negative electrode sheet is rolled and cut to complete the production of the button battery negative electrode sheet.

[0123] 2) Button battery production: The prepared negative electrode plate, separator, electrolyte and lithium sheet are placed in a shell, and a CR2032 button battery is prepared by sealing and pressing. The separator is a PP / PE composite separator, and the electrolyte composition is: 5wt% FEC is added to the EC / DMC / EMC (volume ratio is 1:1:1) solution, and 1M lithium hexafluorophosphate is used as a lithium salt to obtain an electrolyte.

[0124] The prepared button cell was subjected to an electrical performance test, and the test process was as follows:

[0125] 1) First cycle reversible capacity: After the button cell is assembled, ① discharge first: 0.1C constant current discharge to 0.01V, the discharge specific capacity is recorded as Q1; ② recharge: 0.1C constant current charge to 2V, the charge specific capacity is recorded as Q2; the charge specific capacity is recorded as Q2, which is the first cycle reversible capacity;

[0126] 2) First cycle coulombic efficiency: After the button cell is assembled, ① discharge first: 0.1C constant current discharge to 0.01V, the discharge specific capacity is recorded as Q1; ② recharge: 0.1C constant current charge to 2V, the charge specific capacity is recorded as Q2; the first coulombic efficiency is the value of Q2 / Q1;

[0127] 3) 100-cycle capacity retention rate: ① Discharge: 0.1C constant current discharge to 0.01V, the discharge specific capacity is recorded as Q1; ② Charge: 0.1C constant current charge to 2V, the obtained charge specific capacity is recorded as Q2; Repeat steps ① and ② for 100 cycles, the charge capacity is Q100, Q100 / Q2 is the 100-cycle capacity retention rate;

[0128] 4) Energy density: Energy density is the charge-discharge capacity at 0.1C multiplied by the platform voltage.

[0129] The specific test results are as follows:

[0130] Table 1 Matrix characterization results

[0131]

[0132] Table 2 Characterization results of negative electrode materials

[0133]

[0134]

[0135] Table 3 Test results

[0136]

[0137] It can be seen from the above data that the application of the negative electrode material of the present application can be beneficial to improving the coulombic efficiency and cycle life of the secondary battery, and can ensure that the secondary battery has a higher energy density.

[0138] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A negative electrode material, characterized in that: include: A substrate having a plurality of pores, wherein the substrate comprises a porous carbon substrate and a graphite material distributed in the porous carbon substrate; a silicon-based material, at least partially distributed in the pores of the substrate; A carbon coating layer distributed on at least a portion of the surface of the substrate; In the dQ / dV differential curve of the button battery made of the negative electrode material, the peak intensity ratio corresponding to 0.40-0.50V and 0.25-0.40V is ≤1; wherein the differential curve is obtained by: at 20-30°C, the button battery is charged and discharged at a rate of 0.1C, the cycle cut-off voltage is 0.01V-2.0V, and the dQ / dV differential curve is obtained from the delithiation curve of the first cycle.

2. The negative electrode material according to claim 1, characterized in that Based on the total mass of the negative electrode material, the content of graphite material is 5wt% to 40wt%, and the content of silicon element is 20wt% to 70wt%.

3. The negative electrode material according to claim 1, characterized in that The negative electrode material has a sphericity of ≥70% and a median particle size of 1 μm to 40 μm.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The graphite material includes at least one of artificial graphite, flake graphite, and microcrystalline graphite; And / or, the median particle size of the graphite material is 0.5 μm to 10 μm.

5. The negative electrode material according to any one of claims 1 to 3, characterized in that: The pore volume of the matrix is ​​greater than 0.7 cm 3 / g, average pore size is 0.1nm~20nm; And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for ≤10wt%; And / or, the specific surface area of ​​the negative electrode material is ≤10m 2 / g.

6. The negative electrode material according to claim 5, characterized in that The pore volume of the matrix is ​​0.7 to 0.95 cm 3 / g; And / or, based on the total mass of the negative electrode material, the mass of the carbon layer accounts for 0.5wt% to 10wt%; And / or, the specific surface area of ​​the negative electrode material is 1 to 10 m 2 / g.

7. The negative electrode material according to any one of claims 1 to 3, characterized in that The silicon crystal size of the Si (111) crystal plane of the negative electrode material is 0.2nm to 20nm.

8. The negative electrode material according to claim 1, characterized in that In the dQ / dV differential curve, the peak intensity corresponding to the range of 0.40 to 0.50 V is 2000 to 4000 mAh·g -1 ·V -1 , the corresponding peak intensity in the range of 0.25 to 0.40 V is 4000 to 6000 mAh·g -1 ·V -1 .

9. A secondary battery, characterized in that: The secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Carbon-silicon negative electrode material and preparation method thereof

    CN112054171A

  • Composite carbon-silicon negative electrode material and preparation method thereof

    CN117577801A

  • Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material

    CN118156450A

  • Silicon-carbon negative electrode material, negative electrode and lithium ion battery

    CN118412459A

  • Silicon-carbon composite material and preparation method thereof, and secondary battery including silicon-carbon composite material

    US20250070169A1